Young athletes' awareness and monitoring of anti-doping in daily life: Does motivation matter? - Chan, Derwin; Donovan, Robert; Lentillon-Kaestner, V.; Hardcastle, Sarah; Dimmock, J.; Keatley, D.; Hagger, Martin (Wiley-Blackwell Publishing, Inc., 2015)
This study was a preliminarily investigation into the prevention of unintentional doping on the basis of self-determination theory (SDT). Specifically, we examined the relationship between athletes' motives for doping avoidance and their behavior when offered an unfamiliar food product. Participants were young Australian athletes (n = 410) that were offered a free lollipop prior to completing a questionnaire. It was noted whether participants refused to take or eat the lollipop and whether they read the ingredients of the lollipop. The questionnaire assessed autonomous and controlled forms of motivation, amotivation, doping intentions, and adherence regarding doping avoidance behaviors. The results showed that young athletes who adopted controlled reasons to avoid doping in sport (e.g., not getting caught) tended to report higher adherence to behaviors related to avoiding and monitoring banned substances, whereas those who adopted autonomous reasons (e.g., anti-doping being consistent with life goals) appeared to be more willing to read the ingredients of the provided food. The significant interaction effect between autonomous and controlled motivation indicated that autonomous motivation was more predictive to doping intention for athletes with low controlled motivation. It is concluded that SDT may help understand the motivational processes of the prevention of unintentional doping in sport.